Clinical phenotypes and genetic features of hereditary transthyretin amyloidosis patients in China - He, Xinyue; Tian, Zhuang; Guan, Hongzhi; Zhang, Shuyang (Orphanet journal of rare diseases, 2022)
Hereditary transthyretin amyloidosis (hATTR) is a progressive and fatal disease with heterogenous clinical presentations, limited diagnosis and poor prognosis. This retrospective analysis study aimed to report the genotypes and phenotypes of herediary transthyretin amyloidosis (hATTR) in Chinese through a systematic review of published literature. The systematic review included structured searches of peer-reviewed literature published from 2007 to 2020 of following online reference databases: PubMed, Web of Science and the literature database in China. Extracted data included sample size, personal information (sex, age, natural course, family history), mutation type, clinical milestones and reason of death. We described 126 Chinese patients with hereditary transthyretin amyloidosis identified through a systematic review of 30 studies. The most common genotype in the Chinese population was Gly83Arg (25, 19.8%), which most likely presented visual and neurological abnormalities without reported death. The second and third most common genotypes were Val30Met (20, 15.9%) and Val30Ala (10, 7.9%). Peripheral neurological manifestations (91, 72%) were dominant in 126 patients. The followed manifestation was autonomic neurological abnormalities (73, 58%). Half of the cases were reported to have visual disorders, and nearly one-third of the cases presented cardiac abnormalities. Among all 126 reported patients, 46.03% were classified as neurological type, 30.16% as mixed type and only 2.38% as cardiac type. In addition. Chinese patients were mostly early onset, with age of onset at 41.8 (SD: 8.9) years, and the median time from onset to death was 7.5 [IQR: 5.3] years. Patients with cardiac involvement had a shorter survival duration (log Rank (Mantel-Cox), [chl].sup.2 = 26.885, P < 0.001). This study focused on 126 Chinese hATTR patients obtained from a literature review. A total of 26 kinds of TTR mutations were found and the most common one was Gly83Arg. As for phenotype, 46.03% were classified as neurological type, 30.16% as mixed type and only 2.38% as cardiac type. Chinese hATTR patients were mostly early onset (AO 41.8 years), and the median time from onset to death was 7.5 years.